Antiviral and anti-inflammatory activity of budesonide against human rhinovirus infection mediated via autophagy activation - Kim, Seong Ryeol; Song, Jae Hyoung; Ahn, Jae Hee; Lee, Geun Shik; Ahn, Huijeong; Yoon, Sung il; Kang, Seung Goo; Kim, Pyeung Hyeun; Jeon, Sang Min; Choi, Eun Ji; Shin, Sooyoung; Cha, Younggil; et al. (Antiviral Research, 2018)
Human rhinovirus (HRV) infection causes more than 80% of all common colds and is associated with severe complications in patients with asthma and chronic obstructive pulmonary disease. To identify antiviral drug against HRV infection, we screened 800 FDA-approved drugs and found budesonide as one of the possible drug candidates. Budesonide is a corticosteroid, which is commonly used to prevent exacerbation of asthma and symptoms of common cold. Budesonide specifically protects host cells from cytotoxicity following HRV infection, which depend on the expression of glucocorticoid receptor. Intranasal administration of budesonide lowered the pulmonary HRV load and the levels of IL-1β cytokine leading to decreased lung inflammation. Budesonide regulates IL-1β production following HRV infection independent of inflammasome activation. Instead, budesonide induces mitochondrial reactive oxygen species followed by activation of autophagy. Further, the inhibition of autophagy following chloroquine or bafilomycin A1 treatment reduced the anti-viral effect of budesonide against HRV, suggesting that the antiviral activity of budesonide was mediated via autophagy. The results suggest that budesonide represents a promising antiviral and anti-inflammatory drug candidate for the treatment of human rhinovirus infection.
Keywords: Administration, Intranasal; Animals; Anti-Inflammatory Agents; Antiviral Agents; Autophagy; Budesonide; Cell Line; Disease Models, Animal; Female; Humans; Inflammation; Interleukin-1beta; Lung; Mice; Mitochondria; Picornaviridae Infections; Reactive Oxygen Species; Rhinovirus; Viral Load; Virus Replication; Autophagy; Budesonide; IL-1β; Reactive oxygen species; Rhinovirus